2013
DOI: 10.4103/0973-1296.117831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NR-Salacia on post-prandial hyperglycemia: A randomized double blind, placebo-controlled, crossover study in healthy volunteers

Abstract: Background:Salacia chinensis (S. chinensis) is widely distributed in India and Sri Lanka. Most of the species of genus Salacia are known to have effects on blood glucose levels; however, the effects of S. chinensis on glucose levels are seldom reported.Objective:To evaluate the oral hypoglycemic activity of NR- Salacia (1000 mg extract of S. chinensis) in healthy adults.Materials and Methods:Randomized, double-blind, placebo-controlled, cross-over study was conducted in healthy volunteers. Single dose of NR-Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The doses of the herbal extract had significant effects on postprandial insulinemia after administration with sucrose solution. The doses of extract for this study are lower than the 1000 mg dose found to be efficacious in other Salacia extracts species studies [ 13 15 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The doses of the herbal extract had significant effects on postprandial insulinemia after administration with sucrose solution. The doses of extract for this study are lower than the 1000 mg dose found to be efficacious in other Salacia extracts species studies [ 13 15 ].…”
Section: Discussionmentioning
confidence: 89%
“…AUC glucose and AUC insulin in the subjects with a fasting blood glucose level between 100 and 125 mg/dL in healthy Japanese volunteers [ 38 ]. In another study [ 13 ], 1000 mg extract of Salacia chinensis was given with carbohydrate-rich diet (approximately 600 Kcal) and AUC glucose decreased and no data are available on insulin. These two studies were reported with a meal and current study is with a sucrose loading as recommended by FDA for alpha-glucosidase inhibitor products and sucrose (rather than starch) was the most appropriate carbohydrate load [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenugreek has been studied for its hypoglycemic effect, and there have been favorable results of its hypoglycemic efficacy [ 24 - 26 ]. S. reticulata has evidence for inhibition of intestinal alpha glucosidase and may have clinical significance in reducing post prandial glucose values[ 27 ]. Goat weed ( S. dulcis ) has been studied widely regarding its intestinal alpha glucosidase inhibitory activity in rat models but clinical trials are lacking [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamon has the largest pool of evidence to date [ 26 ]. Selacia reticulata has evidence for inhibition of intestinal alpha glucosidase and may have clinical significance in reducing postprandial and fasting plasma glucose (FPG) values [ 27 - 29 ]. Evidence of efficacy for bitter melon is similar with some studies showing improvements in FPG and postprandial plasma glucose [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%